Perkembangan Pendidikan di Indonesia - Zamhari Zamhari; Dwi Noviani; Zainuddin Zainuddin (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Education is a key element in the development of society and the country. This article examines the development of education in Indonesia with a focus on the background, results and conclusions of the historical journey of education in this country. The development of education in Indonesia has been influenced by a long history, especially the period of Dutch colonialism. Education at that time was limited to the native elite and created inequality in access to education. However, after the proclamation of independence in 1945, education became a top priority in national development, resulting in a significant increase in access to basic education. Nevertheless, educational inequality between urban and rural areas and between islands in Indonesia remains a problem that must be addressed..Educational developments in Indonesia include increasing access to education, diversifying higher education programs, and efforts to integrate local culture in the curriculum. The government has allocated a significant budget for education, modernizing the curriculum and improving the quality of teaching. Education reform also includes teacher training and curriculum updates to face changing times. However, there are still challenges in educational governance, unequal access to education, and integrating technology in the learning process. The development of education in Indonesia reflects a journey full of challenges and significant changes. While there has been progress in terms of access and cultural integration efforts, challenges such as educational inequality, complex governance, and technology integration still need to be addressed. Quality education remains a priority, with the hope that continued efforts will ensure that education in Indonesia meets high quality standards and is relevant to face a challenging future. Keywords: Education, Indonesia, History